Increasing the Wear Resistance of Structural Alloy Steel 38CrNi3MoV Subjected to Isothermal Hardening and Deep Cryogenic Treatment - Serhii Bobyr; Pavlo Krot; Eduard Parusov; Tetiana Golubenko; Olena Baranovs’ka (Applied Sciences, 2023)
In the production of critical parts for various machines and mechanisms, expensive structural steels are used alloyed with chromium, nickel, molybdenum, and vanadium. In practice, the wear resistance of parts, especially under severe operating conditions, may be insufficient due to uneven microstructure and the content of retained austenite. Therefore, increasing the operational stability of various products made of alloy steels is an important task. The purpose of this work is to investigate the effect of isothermal hardening from the intermediate (γ+α)-area and the duration of deep cryogenic treatment on the structure formation and frictional wear resistance of 38CrNi3MoV steel. The isothermal hardening promotes the formation of the required multiphase microstructure of 38CrNi3MoV steel. The influence of the duration of deep cryogenic treatment on the microhardness, amount of retained austenite, fine structure parameters, and friction wear of 38CrNi3MoV steel are established. Complex heat treatment of 38CrNi3MoV steel, according to the proposed mode, makes it possible to achieve a significant decomposition of retained austenite to martensite, which leads to an increase in frictional wear resistance of ~58%.